2018
DOI: 10.3389/fgene.2018.00237
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction of Breeding Values Using a Subset of SNPs Identified by Three Machine Learning Methods

Abstract: The analysis of large genomic data is hampered by issues such as a small number of observations and a large number of predictive variables (commonly known as “large P small N”), high dimensionality or highly correlated data structures. Machine learning methods are renowned for dealing with these problems. To date machine learning methods have been applied in Genome-Wide Association Studies for identification of candidate genes, epistasis detection, gene network pathway analyses and genomic prediction of phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 68 publications
8
128
3
4
Order By: Relevance
“…The authors stated that "adding non-signal predictors can adversely affect the predictive accuracy of the non-linear regression models". Other studies have shown the interest of machine learning methods for genomic prediction [59][60]. In our study, this was not the case for RKHS, but for SVM and BRNN.…”
Section: Plos Onementioning
confidence: 55%
“…The authors stated that "adding non-signal predictors can adversely affect the predictive accuracy of the non-linear regression models". Other studies have shown the interest of machine learning methods for genomic prediction [59][60]. In our study, this was not the case for RKHS, but for SVM and BRNN.…”
Section: Plos Onementioning
confidence: 55%
“…The availability of large amount of genomic resources and high-density genotyping data has facilitated the successful implementation of GS in chickpea (Roorkiwal et al , 2018bLi et al 2018). Phenotyping and genotyping data collected from 320 elite breeding lines were combined with six statistical GS models to evaluate prediction accuracies.…”
Section: Genomic Selection For Selecting Loci With Relatively Small Gmentioning
confidence: 99%
“…Prominent results were evident from the high prediction accuracies (up to 0.91) obtained for diverse yield and its component traits for GS in chickpea breeding . A recent GS study suggested the possibility of increasing prediction accuracies for complex traits like drought by incorporating GWAS results into GS models (Li et al 2018). This study also provided evidence that the application of GS models using a subset of SNPs closely associated with the trait, in contrast to all SNPs, can increase prediction accuracies by several folds for yield-related traits.…”
Section: Genomic Selection For Selecting Loci With Relatively Small Gmentioning
confidence: 99%
“…With FS, it is possible to reduce marker density and build simpler and more comprehensive models 46 , thereby increasing predictive power due to the identification of phenotype-associated polymorphisms. A few previous studies applied ML methods to decrease the number of SNP datasets needed for phenotypic predictions [47][48][49] , achieving high accuracy. The identification of such a subset of putative causal polymorphisms is crucial for improving production in plants 42 and represents a novel strategy for genomic prediction in sugarcane.…”
Section: Introductionmentioning
confidence: 99%